Application of the vacuum method to obtain graphite - Avliyakulov Khayot Nodirovich; Bafoev Bakhrom Botirovich (Zien Journals, 2022)
The article discusses the conceptual requirements for deposition methods widely used in modern microelectronics. The high deposition rate and the atomic energy incident on the substrate during deposition allow these methods to be used to obtain films with various compositions and structures, especially for low temperature epitaxy.
Keywords: Thermal spraying; resistive spraying; layered system; defect